2015
DOI: 10.1111/os.12169
|View full text |Cite
|
Sign up to set email alerts
|

Sternal Tumor Resection and Reconstruction with Titanium Mesh: a Preliminary Study

Abstract: Titanium mesh chest reconstruction after sternal tumor resection has the advantages of simplifying the procedure, achieving a good shape and having few complications. Titanium mesh is an ideal material for reconstruction of the sternum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 23 publications
(23 reference statements)
0
27
0
1
Order By: Relevance
“…To our knowledge, only 13 patients with SS-LCH of the sternum have been reported (10)(11)(12). It is interesting that most SS-LCH patients were female (male:female:unknown ratio, 2:9:2), which was in direct contrast to the male to female LCH ratio.…”
Section: Case Presentationmentioning
confidence: 43%
“…To our knowledge, only 13 patients with SS-LCH of the sternum have been reported (10)(11)(12). It is interesting that most SS-LCH patients were female (male:female:unknown ratio, 2:9:2), which was in direct contrast to the male to female LCH ratio.…”
Section: Case Presentationmentioning
confidence: 43%
“…Bone banks are available only in select healthcare delivery centers. Titanium mesh is well tolerated without much of complications and suitable for large sternal defects [7]. Titanium mesh we used in the second case was essential due to size of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Sternal tumors are rare, comprising only 0.94% of all bone tumors, with the majority being sarcomas. 1 The most common sternal tumors are chondrosarcomas, followed by osteosarcoma, myeloma, and malignant lymphoma. Patients present with variable symptoms, including chest pain, palpable mass, and signs of swelling.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Radical or extended resection has become the gold standard for treating sternal tumors because it reduces the chances of local recurrence. 1 , 2 , 4 However, even with radical resection and reconstruction, survival rates remain low for patients with primary sternal tumors. A study of 36 patients who underwent sternal resection of primary malignant tumors reported that the overall 5-year survival rate for resection and reconstruction was 66% (low–intermediate grade: 77%; high grade: 47%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation